2018
DOI: 10.1016/j.jtho.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Advances and New Frontiers in Mesothelioma Therapeutics

Abstract: Malignant pleural mesothelioma (MPM) is a rare and aggressive cancer that arises from the mesothelial surface of the pleural and peritoneal cavities, the pericardium, and rarely, the tunica vaginalis. The incidence of MPM is expected to increase worldwide in the next two decades. However, even with the use of multimodality treatment, MPM remains challenging to treat, with a 5-year survival rate of less than 5%. The International Association for the Study of Lung Cancer has gathered experts in different areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 126 publications
(129 reference statements)
0
87
0
Order By: Relevance
“…Clinical trials using cytotoxic T‐lymphocyte–associated protein 4 (CTLA‐4) inhibitors failed to improve survival in mesothelioma . Subsequent trials suggested that PD‐L1 inhibitors may benefit some patients .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials using cytotoxic T‐lymphocyte–associated protein 4 (CTLA‐4) inhibitors failed to improve survival in mesothelioma . Subsequent trials suggested that PD‐L1 inhibitors may benefit some patients .…”
Section: Treatmentmentioning
confidence: 99%
“…A priority is the identification of biomarkers that predict benefit or harm from immune checkpoint inhibitors. Reported toxicities are comparable to the use of immunotherapy in other tumors and can be managed with the standard of care . Other aspects of the antitumor immune response are being targeted in smaller studies and include vaccines, autologous T cells, chimeric antigen receptor T cells, and viral therapies.…”
Section: Treatmentmentioning
confidence: 99%
“…The standard treatment for unresectable, advanced malignant mesothelioma is chemotherapy, although with a very poor prognosis. 36 Similar to its use in non-smallcell lung cancer, 37-44 cisplatin (CDDP) and pemetrexed (PEM) combination therapy (CDDP/PEM) approved by the US Food and Drug Administration (FDA) in 2004, is strongly recommended as the first-line treatment for mesothelioma. 45 Moreover, molecularly targeted agents have been developed to augment cytotoxic chemotherapy.…”
Section: Icis In the First-line Settingsmentioning
confidence: 99%
“…Even if the use of asbestos is now banned in several countries, the mean latency period between asbestos exposures to the time of mesothelioma diagnosis has been determined to range between 20 and 40 years (H. H. Sun et al, ). Due to this long latency, it is expected that, in the next decades, asbestos‐induced mesothelioma incidence will persist (Mutti et al, ).…”
Section: Introductionmentioning
confidence: 99%